Design of a model-based criteria and characteristics for the evaluation of archives websites - Sanz Caballero, Isabel; Faba Pérez, Cristina (Revista General de Información y Documentación, 2012)
Archives cannot be left out the Internet as the Web has become an indispensable tool for the development of the societies and to publicize the services and products that the institutions offer. This openness and diffusion of the archive through the Internet has also brought the need to check what level of quality they present. To do that it is necessary to evaluate them and to attend to some indicators or specific features related to their design, structure or contents. The main target of his work is to design a comprehensive template of specific characteristics for the evaluation of archive websites. The results and conclusions of this work demonstrate that it is possible to design a specific model of features determining which ones are those that best represent the quality of an archive on the Web.